The optimization of engine operating parameters via SWARA and ARAS hybrid method in a small SI engine using alternative fuels - SAYIN, CENK (ELSEVIER SCI LTD, 2020)
In most countries, mandatory emission norms have been established to reduce greenhouse gas emissions. In addition, the production and use of diesel engines with high emissions have been prohibited in some countries. For this reason, spark ignition (SI) engines have become important. Research on the use of renewable energy sources and the development of energy-efficient engines is increasing in terms of sustainability. It is known that alcohol fuels with high knock resistance than gasoline generate higher engine efficiency under different engine operating conditions. In this study, it is determined that the optimum operating parameters of an SI engine fueled with pure ethanol and methanol as an alternative fuel in terms of performance, emission and combustion characteristics. The engine tests were used an air-cooled and single-cylinder small SI engine. The engine has been set to three different ignition timing/advance (IT), compression ratio (CR) and air excess coefficient (AEC), and tested in varied combinations. In a total of eighty-one different test conditions, the engine was operated at the full-throttle opening and at engine speed at 2400 rpm with test fuels, and then performance emission and combustion data were obtained. The optimal operating parameters are determined with a multi-criteria decision-making method (MCDM) using a total of seven hundred twenty-nine experimental data. For this purpose, SWARA-ARAS (Step-wise Weight Assessment Ratio Analysis-Additive Ratio Assessment) hybrid method is preferred. According to the results, the optimum working parameters were found to be 9.0:1 of CR, 1.1 of AEC, and 20 degrees crankshaft angle (CA) of IT in the use of pure methanol fuel. In addition, the top ten rankings entering the operating parameters are presented in the article. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: The optimum operating parameters; Ethanol; Methanol; Compression ratio; Air excess coefficient; Ignition timing; ARAS; SWARA; MCDM; SPARK-IGNITION ENGINE; ALCOHOL-GASOLINE BLENDS; PERFORMANCE; EMISSIONS; SELECTION; METHANOL; ETHANOL; RATIO; COMBUSTION